Blades of Faith and Beauty: Symbolism and Ornamentation on Daggers and Arms in the Islamic Heritage of the Pakistan Region - Latif, Ayesha; Ahmed, Nabeel; Yazdani, Sami (ACADEMIA International Journal for Social Sciences, 2025)
This paper will explore the development of Islamic weapons in Pakistan, 16th -19th centuries, but with a different perspective; it does not consider the weapons as mere tools of war; it views them as vessels of "faith and beauty" which are well-developed. Though traditional scholarship has tended to group South Asian weapons by some broad terms like Islamic or Indian, in this study, the approach taken is to be localised to determine the specific martial identity of the Indus Valley. Through the application of Art and Design theoretical framework, the methodology incorporates a formal analysis, materiality and semiotics in decoding the structural and symbolic layers of daggers and swords. The major discoveries indicate that the decoration of these blades of faith was a two-fold purpose: as spiritual protection where Quranic writings (e.g. the Throne Verse) and mystical signs of the Seal of Solomon were inscribed and also serving as symbols of the imperial status in the Mughal Mansabdari system, jewelled daggers were granted as a symbol of royal patronage. In addition the paper also determines the regional peculiarities e.g., the Sindh matchlock and tracks the artisanal persistence of metallurgical skills in historical gateways, including Sialkot, Lahore and Gujrat. The study concludes that the historical shift of mediaeval lohar (armourer) skills into current worldwide industrial exhibits, e.g. the surgical instrument sector in Sialkot, is an important segment of the industrial history of Pakistan. As the artefacts are placed in a transregional nexus of Persian, Ottoman, and local influences, the study has added a subtle regional discourse into the wider area of the study of Islamic material culture and heritage.